THE CORRELATION NITRATE LEVELS AND NITRIC OXIDE (NO) IN BLOOD AS A RISKY FACTOR OF TYPE 2 DIABETES MELLITUS WITH HYPERTENSION AT RSUP DR. SARDJITO OF YOGYAKARTA - Fransisca Shinta Maharini; Ahmad Hamim Sadewa; Pramudji Hastuti (Jurnal Kesehatan Prima, 2018)
Abstract: Diabetes Mellitus (DM) is a metabolic disease characterized by hyperglycemia caused by insulin secretion disorder, insulin function or both of them. Hypertension is a disease identified by the increasing of diastolic blood pressure ≥90 mmHg or systolic blood pressure ≥140 mmHg. Diabetes mellitus and hypertension are two closely related condition and both are health problems which require accurate treatment, since it may accelerate complication of DM and hypertension. The occurrence of  DM and hypertension is higher than solely DM. DM causes hyperglycemia that triggers oxidative stress, increasing NO degradation leads to hypertension.This research utilized a case-control study involving with type 2 DM with hypertension patients as the case (n = 40) and type 2 DM without hypertension as the control groups (n = 40). The level of NO was analyzed using spectrophotometry. Correlation regression was used to analyzed the correlation between NO and blood pressure. A p value ˂ 0,05 was considered as significantly differance. The results showed mean level of NO was lower on subjects type 2 DM with hypertension compared to that of on subjects with type 2 DM without hypertension (p=0,023). There was a negative and week correlation between the level of NO and blood pressure (Systolic r = -0.233, p=0.037 and Diastolic r = -0.149, p=0.188).Keywords: Type 2 DM; Hypertension; Nitric Oxide.